A Pragmatics Perspective Of Figurative Language Used In Al-Quran (Al-Baqarah) - Cahyaningsih, Laila Indah; , Drs. Maryadi, M.A; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research paper is about an analysis of figurative language used in Al-Quran. The major problems in this study are to know the types of figurative language used in Al-Quran, to know the meaning of figurative language found in the Al-Quran and to reveal the dominant figurative language in the Al-Quran. The primary sources of data are the research is conducted by using descriptive qualitative research. The method of the data collection is documentation. Based on the research, the researcher concludes that in analyzing literary work, especially Al-Quran, the researcher uses a part of whole figures of speech; they are simile, personification, symbol, hyperbole, and metaphor. Based on the analysis, the study reveals that there are many meanings and types of figurative language in Al-Quran. The dominant figurative language in Al- Quran is simile and his minor figures of speech are personification, symbol, hyperbole, and metaphor. The meaning revealed from the Al-Quran conventional implicature and conversational implicature.